TIPOLOGI DESA DAN KOMODITAS UNGGULAN DALAM PENERAPAN AGROPOLITAN DI DESA PA'RAPPUNGANTA KABUPATEN TAKALAR - Siradjuddin, Irsyadi; Anshar, Muhammad; Idham AP., Andi (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2021)
Abstract. Pa'rappunganta Village, Takalar Regency is a village with a dense population and needs to develop sustainable rural areas in the context of developing an agropolitan area. To optimize the potential of the agricultural sector in the application of the agropolitan concept, it is necessary to identify the village typology and superior commodities in Pa'rappunganta Village, Takalar Regency. This study aims to identify village typology and superior commodities in Pa'rappunganta Village. The research place in Pa'rappunganta Village, North Polongbangkeng District, Takalar Regency. The research was conducted from March 2019 to June 2019. Data collection was carried out by observation, surveys and literature study. The research analysis used is the analysis of village typology, LQ analysis, and Shift Share analysis. The results showed that the Typology of Pa'rappunganta Village was Self-Sufficient. Pa'rappunganta village has complete indicators in production (village output), culture, education and skills, as well as self-help and cooperation. Superior commodities of Pa'rappunganta village are corn and chili. Both commodities have value as a base sector and progressive growth.